Lipoids and blood platelets with reference to blood coagulation and the hemorrhagic diseases - Ferguson, John Howard (Division of Physiological Sciences, 2020)
By specifically analysing for the various active principles of plasma, platelets, tissues and their fractions, much new information has been obtained concerning the role of lipoids and platelets in blood coagulation and in the hemostatic mechanisms in health and disease. Analysed components are studied in artificial clotting systems, especially a two-stage thrombin- forming system. Some 86 cases of bleeding disorders, 32 new born normal infants and their mothers, and many normal adult bloods have been analysed with respect to components of the clotting and hemostatic functions. The detailed considerations embodied in the thesis are encompassed under the following heads: 1) the importance of certain lipoids, especially cephalin 2) the normal need, in plasma clotting, for platelets, 3) the particular significance of a platelet component, which has many analogies to cephalin, in the thromboplastic system, 4) potentiation of the thromboplastic actions of cephalin, of platelets, and of tissue thromboplastin (to some extent) by a variety of experimental additives. Part of this may be explained as a 'thromboplastin generation' through co-participation of certain plasmatic components (antihemophilic globulin, PTC" etc. ) . Part, however, may be the result of certain proteolytic enzymes, particularly trypsin, 'disaggregating' lipoproteins and thus rendering their phospholipid (and sometimes calcium) available for participation in the clotting reactions, 5) possible Ca-containing and lipid-containing 'intermediates’ in the thrombin-forming reactions, 6) myelin figure formation as an explanation of ‘alterations' of platelets and certain other formed elements such as thrombocytes, megakaryocytes, and stromatolytic erythrocytes 7) the multiplicity of factors which platelets may contribute to the blood clotting and hemostatic mechanisms 8) the occurrence of many clinical disorders due to deficiency of platelet functions. Thrombocytopenias denote deficient numbers ('counts' and total bulk in body). Thrombocytopathies are deficiencies of specific platelet components, e . g. thromboplastic factor, accelerator, vasoconstrictor (5-hydroxy tryptamine), or retractor factor. Such deficiencies can be clinically significant even when the platelet count is normal. Bleeding in leukaemias, uremias, etc. may often be accounted for in these terms, 9) the nature and modes of action of heparin and other 'antithromboplastic’ inhibitors, and of some antiproteases, in relation to the mechanisms discussed 10) the ‘cephalin availability theory' of the author, as a useful working hypothesis to explain the importance of the natural thromboplastic phospholipid. Lipid release from platelet, tissue, or possibly plasma sources may very well be the long-obscure 'trigger mechanism' which initiates blood coagulation.